Health and Popular Psychology: Ayurveda in the Western Holistic Health Sector - Warrier, Maya (Religions of South Asia, 2018)
This article examines a small selection of popular anglophone publications on ayurveda, authored by three well-known US-based writer-practitioners: Robert Svoboda, Deepak Chopra and David Frawley. It argues that these individuals' interpretations of ayurveda's principles and practices are deeply influenced by popular psychology, and by the therapy culture that it has spawned in Euro-American contexts. These writers draw upon some key tenets of popular psychology in their works: that physical illness is an outward manifestation of a psychological problem; that self-awareness and personal growth are essential for attaining optimum health; that individuals must assume active responsibility for maximizing health and wellbeing. Through their psychologized interpretations, Chopra, Frawley and Svoboda greatly expand ayurveda's scope. In their hands, ayurveda is not simply a medical tradition for remedying illness (its predominant focus in mainstream South Asian practice) but, more importantly, a means for personal growth, human potential optimization, and self-actualization.